Crystal engineering and sorption studies of cyclotriveratrylene and C-methylcalix[4]resorcinarene solvates - Payne, Richard Michael (Department of Chemistry, 2020)
Cyclotriveratrylene compounds crystallised from acetonitrile (1) and 2-butanone (4) are shown to be nearly isostructural, resulting in the formation of dimeric capsules, while the compound which crystallised from chloroform (3) results in the formation of layers of cyclotriveratrylene molecules separated by layers of chloroform molecules. 1 is found to undergo a single-crystal-to-single-crystal transformation following desolvation. Consecutive single-crystal X-ray diffraction experiments on 1 at 50 °C reveal that the rotation of a unique, single methoxy group of the host molecule may permit the escape of the solvent molecules from the apparently nonporous crystal. C-methylcalix[4]resorcinarene has been shown previously to form either channel-type structures or hexameric, spherical assemblies when crystallised from various alcohol molecules. The effect of the length of the alkyl chain of the solvent alcohol was studied. It was established that the short-chain alcohols favour the formation of channel-type structures while the longer-chain alcohols favour the formation of the hexameric, spherical assemblies. A hexameric assembly structure crystallised from 1-propanol (8) displays a ~25% increased interior volume over known assemblies and is found to be the first of these types of assemblies to form by vapour sorption. A hexameric assembly structure crystallised from 1-butanol (9) has already been published in the literature. However, SCXRD studies for this work revealed additional structural information not apparent in the literature structure. Another hexameric assembly structure, this time crystallised from 1-pentanol (10), was shown to be similar to the structure of 9, with certain differences. Characterization of these structures was performed by single-crystal X-ray diffraction, powder X-ray diffraction, hot stage microscopy and thermal analysis. All compounds were shown to maintain crystallinity upon heating and desolvation – however, several transitioned through an amorphous phase. Gas and vapour sorption analysis was performed on all activated compounds. Some of these compounds were found to resolvate to their original solvated structures merely upon exposure of the desolvated powders to the solvent vapours.